Dynamic analysis of the determinants of long-term microfinance interest rates: Macro and micro factors - Rauf, Fawad; Wanqiu, Wang; Jing, Li; Qadri, Syed Usman; Naveed, Khwaja; Rahman, Shams U. (Frontiers in Psychology, 2022)
Introduction A recent increase in interest rates has raised doubts about the stability of micro-finance institutions (MFI) A recent increase in interest rates has raised doubts about the stability of MFI in many countries. This has compelled governments to consider some MFI practices unethical. Methods This paper studies the MFI interest rates by using a dynamic panel method to identify the determining factors of the viability, financial, and social execution of microfinance firms. The research shows that the long-term interest rate evolution depends on the anticipation of loan loss rates (LLR), profit, or macroeconomic factors like inflation and the short-term current interest rate. The Study used database of 897 microfinance institutions in 106 countries and six geographic regions with a representative sample size of 5,075 observations between 2008 and 2020. The external factors considered are the market structure (Competition), economics (inflation), cultural and technological political conditions, and banking regulations in effect (regulation). Financial costs, operational costs, the write-off rate, and the average size of the loan are the most important determinant factors in MFI interest rate fluctuations. Results The research find that other factors like gender, legal status, and regulations also contribute to the MFI interest rate variation. The research also discovered that there is a threshold effect in the relationship between women borrowers (WB) and the interest rate. Another important finding of this study is that MFIs do not anticipate inflation in the definition of the interest rate. Discussion From an institutional point of view, it is necessary to promote competition, as the study shows that well-regulated competition helps to keep interest rates at a reasonable level.